1999
DOI: 10.1021/jp991254d
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Supramolecular Structures ofN-Phenyl Formamide and its Hydrated Clusters

Abstract: The amide, N-phenyl formamide (formanilide), and its water clusters have been studied in a jet expansion using laser-induced fluorescence excitation and mass-selected, resonant two-photon ionization (R2PI) techniques. The isomer with a trans configuration of the amide group (defined in Figure ) is identified through analysis of the partially resolved contour of its S1 ← S0 band origin. Ion-dip “hole-burn” spectra of the nonplanar cis isomer contain either symmetric or antisymmetric components of low-frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
151
2
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(170 citation statements)
references
References 28 publications
(63 reference statements)
16
151
2
1
Order By: Relevance
“…As a consequence the energy difference between the synoid and the anti rotamers (⌬E conf ) can be estimated to be about 8.4 kJ/mol, the anti species being the more stable. Ab initio calculations at the MP2/6-31G* level, performed by Dickinson et al (11), led to almost identical stabilities of the two isomers, a result not in agreement with the experimental evidence. They also found, recording R2PI holeburning spectra, that the ground state of the synoid conformer was split into two sublevels, due to a small barrier to planarity between two equivalent synoid forms with the formyl group above or below the benzene plane.…”
Section: Ab Initio and Model Calculations Explain The Failure To Obsementioning
confidence: 85%
See 2 more Smart Citations
“…As a consequence the energy difference between the synoid and the anti rotamers (⌬E conf ) can be estimated to be about 8.4 kJ/mol, the anti species being the more stable. Ab initio calculations at the MP2/6-31G* level, performed by Dickinson et al (11), led to almost identical stabilities of the two isomers, a result not in agreement with the experimental evidence. They also found, recording R2PI holeburning spectra, that the ground state of the synoid conformer was split into two sublevels, due to a small barrier to planarity between two equivalent synoid forms with the formyl group above or below the benzene plane.…”
Section: Ab Initio and Model Calculations Explain The Failure To Obsementioning
confidence: 85%
“…The anti and syn species (see Fig. 1) of FA have indeed been observed either in a chloroform solution (with about the same abundance) (10), or in the gas phase, with the abundance of the syn isomer estimated to be 6.5% (8,11). We thought that the rotational spectrum would have given a precise answer on the structure, conformation, and potential energy surface of the internal rotations in the proximity of the peptidic group of FA.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…The dipole moment measurements, X-ray and neutron diffraction studies demonstrated that the trans conformer of Nphenylacetamide is the predominant and most stable [14,15,39,[41][42]. The influence of the ring substituent on N-H stretching frequency of N-phenylacetamide and its derivatives may be the resultant steric effect, direct field effects, hydrogen bonding and bond polarisation effects [43].…”
Section: Amide Group Vibrationsmentioning
confidence: 99%
“…Spectroscopic and crystal structural studies give valuable informations on bond properties. The -CO-NH-group adopts a planar 'peptide-like' conformation, as in the case of formamide [10], methyl hydrazinocarboxylate [11], N-methylformamide [12], o-methyl acetanilide [13] and formanilide [14,15].…”
Section: Introductionmentioning
confidence: 99%